Reducing Poverty through Growth and Social Policy Reform in Russia - Shaban, Radwan; Asoaka, Hiromi; Barnes, Bob; Drebentsov, Vladimir; Langenbrunner, John; Zurab, Sajaia; Stevens, James; Tarr, David; Tesliuc, Emil; Shabalina, Olga; Yemtsov, Ruslan (Washington, DC: World Bank, 2012)
Following the 1998 financial crisis, four out of every ten people slipped into poverty, not able to meet basic needs. Luckily, post-crisis economic rebound was impressive and broad-based, albeit uneven across sectors and regions. This title explores the nature of poverty, both nationally and regionally, to identify the groups with a high poverty risk. It then examines growth-poverty linkages through the labor market, as well as the contribution of growth and inequality to the recent poverty reduction. It also considers the expected impact of WTO accession on overall growth and poverty. Finally, it focuses on the scope for improving social policy in ways that will have a direct impact on the poor.